Cadmium accumulation in neuronal cells leads to essential metals imbalance and zinc transporters dysregulation - Federica Bovio; Melissa Ferrian; Antonia Franceschi; Pasquale Melchioretto; Stefano Porru; Matilde Forcella; Paola Fusi; Chiara Urani (Toxicology, 2026)

Morphological and metabolic changes in microglia exposed to cadmium: Cues on neurotoxic mechanisms - Federica Bovio; Elisa Perciballi; Pasquale Melchioretto; Daniela Ferrari; Matilde Forcella; Paola Fusi; Chiara Urani (Environmental Research, 2024)

Manganese Benefits Heat-Stressed Corals at the Cellular Level - Enrico Montalbetti; Tom Biscéré; Christine Ferrier-Pagès; Fanny Houlbrèque; Ivan Orlandi; Matilde Forcella; Paolo Galli; Marina Vai; Davide Seveso (Frontiers in Marine Science, 2021)
The intensity and frequency of coral bleaching events have increased worldwide especially due to thermal stress and seawater pollution. Although it has been observed that metal concentration in seawater can affect the coral’s ability to adopt cellular defensive mechanisms to counteract bleaching, more investigations are needed to better understand the role of metals in coral physiology. In this study, we analyzed the individual and combined effects of prolonged heat stress and manganese (Mn) and iron (Fe) enrichments at the cellular level on the coral Stylophora pistillata . Thermal stress caused an up-regulation in the expression of the host Heat shock proteins (Hsps) 60 and 70, which showed a parallel pattern of modulation in all treatments, as well as an increase of lipid peroxidation (LPO) in the holobiont. Fe enrichment did not induce any change in Hsp expression or in the oxidative status of the corals both at the ambient temperature of 26°C or at increased temperature, suggesting that Fe didn’t seem to play a role in mitigating the cellular damages and the coral bleaching. Mn or MnFe enrichment at 26°C seemed to increase the oxidative stress in zooxanthellae, since high LPO and glutathione reductase (GR) levels were recorded, but it did not cause any effect on polyp Hsp expression, probably due to the antioxidant action of GR. With the temperature increase, Mn enrichments prevented any increase in Hsp levels and caused a significant decrease of LPO and GR activity, strengthening a previous hypothesis suggesting that Mn could mitigate the negative cellular effects produced by the thermal stress.